Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/app122211351
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Assessment of Mineral Resource Potential in a Hg-Sb-Pb-Zn Mining Area: The Almadén and Guadalmez Synclines (South-Central Spain)

Abstract: The geochemical data from surface soils are often neglected or questioned when prospecting for ore deposits within active mining districts due to the “background noise” produced by anthropogenic pollution derived from mining activity. Large datasets on a national and international scale offer interesting possibilities to discover prospective zones. In the present work, data from the Geochemical Atlas of Castilla–La Mancha were treated in an area with an intense history of mining Hg, Pb, Zn, and Sb: the Almadén… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Figure 2 shows the distribution of the concentrations of some elements of mining interest according to the geological domain to which they belong: the Alcudia anticline and the Almadén and Guadalmez synclines. As described by Barquero et al ( 2022 ), there are clear differences in terms of the presence of metallic mineralizations between these domains, with Hg mineralizations predominating in the Almadén syncline, Sb in the Guadalmez syncline, and Pb–Zn in the three domains, although with a greater presence in the Alcudia anticline and with high concentrations of Cu in the Guadalmez syncline (Higueras et al 2016 ). It can be observed that all the elements presented have similar averages in the three geological domains, although significant differences are evident in the Hg outliers in the Almadén syncline (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Figure 2 shows the distribution of the concentrations of some elements of mining interest according to the geological domain to which they belong: the Alcudia anticline and the Almadén and Guadalmez synclines. As described by Barquero et al ( 2022 ), there are clear differences in terms of the presence of metallic mineralizations between these domains, with Hg mineralizations predominating in the Almadén syncline, Sb in the Guadalmez syncline, and Pb–Zn in the three domains, although with a greater presence in the Alcudia anticline and with high concentrations of Cu in the Guadalmez syncline (Higueras et al 2016 ). It can be observed that all the elements presented have similar averages in the three geological domains, although significant differences are evident in the Hg outliers in the Almadén syncline (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…It is necessary to highlight the absence of notable differences between domains for Sb (Fig. 2 d), since it is an element which has been mined almost exclusively in the Guadalmez syncline, in addition to being an element with low mobility and very low bioavailability (Barquero et al 2022 ). The most reasonable interpretation is that Sb levels in Quercus leaves correspond to local background levels for this element in these lithological units, slightly higher than the local background levels in the Colline Metallifere (Monaci et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations